PENDALAMAN MENGENAI LAPORAN KEUANGAN UNTUK SISWA/I SMA - Wijoyo, Amin; Patricia, Ivonne; Jonathan, Michelle Leevia; Sylvia; Theodore; T, Alvin (Jurnal Serina Abdimas, 2024)
In the era of information and globalization that continues to grow, understanding financial reports has become an essential skill for the next generation. Financial reports are an alternative to determine the financial health of a company. By realizing how important financial reports are, we intend to deepen the material at Tarsisius 1 High School, West Jakarta. This is because the current high school education curriculum teaches accounting material in class XII so the material explained is less detailed. In fact, basic accounting material is an important foundation for accounting knowledge which should be taught from the start of high school. The deepening of this material was carried out at Tarsisius I High School, West Jakarta with a total of 10 meetings with a duration of one hour and thirty minutes, to be precise every Wednesday from 14.30 WIB to 16.00 WIB. The deepening of the material regarding financial reports was carried out at the 5th meeting on Wednesday, October 4 2023. This study begins with an introduction to the theory of financial reports, discussion of example questions, and implementation of a quiz with prizes. The material discussed in this activity includes the meaning of financial reports, the purpose of making financial reports, the types and differences of each financial report, and procedures for preparing financial reports. After the in-depth study of this material is complete, Tarsisius High School students will receive benefits in the form of increased knowledge and insight. Apart from that, students also have skills in preparing financial reports and are able to explain the relationship between financial reports and previous journals as a whole part of the service company's accounting cycle.